Analysis of Students’ Critical Thinking Skills on the Material of Viruses and their Roles - Sri Handayani; Suranto; Umi Fatmawati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Critical thinking skills are important for students in learning and real life to face the increasingly complex challenges of the 21st century, including those related to viruses. This study aims to analyze students' critical thinking skills on the material of viruses and their roles. This research is a quantitative descriptive research. The research subjects were 70 students from two grade X classes at a Karanganyar, Central Java school, comprising 35 students. The data collection method is done through a written test. The research instrument in the form of essay questions consists of 6 questions based on aspects of critical thinking skills. The data analysis technique used Rasch analysis through the Winsteps 3.73 program. The results of the study show that there are still many students who are unable to answer critical thinking skills questions as seen based on the Wright Map and the comparison of mean logit person (-0.77) < mean logit item (0.00) in the Winsteps output. In conclusion, students' critical thinking skills on virus material are still low. Therefore, further research is needed to improve students' critical thinking skills. Keywords: analysis, critical thinking skills, virus